Is Preeclampsia an Independent Predictor of Diastolic Dysfunction?: A Retrospective Cohort Study [167]. (May 2015) - Guirguis, George; Aziz, Michael Matean; Williams, Shauna F.; Boccia-Lang, Claire; Bilinski, Robyn T.; Shah, Leena Pritesh
Abstract : INTRODUCTION: To determine whether preeclampsia is an independent predictor of diastolic dysfunction and what factors among patients with preeclampsia are associated with diastolic dysfunction. METHODS: This is a retrospective cohort study of patients who delivered between 2008 and 2013 at a single institution who had a maternal echocardiogram during their pregnancy or within 5 months of delivery. Patients with structural heart disease, ejection fraction less than 45%, pulmonary embolus, or age older than 45 years were excluded. Medical records were reviewed for medical and obstetric complications and echocardiogram findings. Demographic characteristics and rate of diastolic dysfunction were compared between patients with preeclampsia and without preeclampsia. Multivariate logistic regression was performed controlling for age, ethnicity, gestational age at delivery, diabetes, preeclampsia, intrauterine growth restriction (IUGR), antihypertensive use, and magnesium sulfate administration. RESULTS: Sixty-six patients were identified; 39 (59%) had preeclampsia. A history of preeclampsia, IUGR in the current pregnancy, antihypertensive use, and magnesium sulfate use was higher in the preeclampsia group. Fifteen (38.5%) in the preeclampsia group were African American compared with two (3%) in the control group ( P <.01). Seventeen (44%) of the patients with preeclampsia were found to have diastolic dysfunction compared with three (11%) patients in a control group (odds ratio 6.18, 95% confidence interval 1.59–24.02; P =.006). Logistic regression analysis did not reveal other independent predictors of diastolic dysfunction. In the patients with preeclampsia, a history of preeclampsia, severe disease, and IUGR were not associated with diastolic dysfunction. CONCLUSION: Our study supports previous findings that preeclampsia is associated with diastolic dysfunction.